Pelletisation of fly ashes as a lightweight aggregate - Derun, E. M.; Tugrul, N.; Lkhagva, T.; Piskin, S. (ICE PUBLISHING, 2010)
This study investigated the use of solid waste fly ash in the production of lightweight concrete. Fly ash is an industrial waste obtained from the coal-fired thermal generating power plant and it is used in the production of additive construction materials. In Turkey more than 15 million tonnes of fly ash is produced each year, but only a small amount is utilised. The industrial waste fly ashes used in this study came from the power plant at Iskenderun Sugozu, Cayirhan, Tuncbilek and Seyitomer. Lightweight aggregate manufactured from the fly ash and Na-bentonite was used in a pelletisation process. The lightweight concrete manufactured from fly ash aggregate was analysed in terms of the slump and density of fresh concrete and the density, compressive strength and tensile splitting strength of hardened concrete. In the present study, the effects of fly ash aggregates from different power plant when used for lightweight concrete production purposes were investigated and the results obtained were quite satisfactory for the related design requirements.
Keywords: CONCRETE; STRENGTH; REUSE; Construction & Building Technology; Materials Science